Specifics of morality at the epoch of liquid modernity - M. M. Rohozha (Ukrainian Cultural Studies, 2019)
The author reveals specifics of the phenomenon of morality in socio-cultural circumstances of liquid modernity. Theoretical constructions of H. Arendt became the methodological grounds for the inquiry. Arendt represented the process of spinning of the web of moral interactions in the concreteness of time and space. The key value transformations of liquid modernity as conditions for the possibility of moral interactions of our time, are defined in the paper. Transformations in the field of economics (labor, employment, consumption) and public space (media, entertainments, discipline) predetermine value changes that define social and moral life of the epoch. These are: freedom from different Modernity-generated restrictions and commitments, opportunity to escape responsibility, and distance from those who were traditionally comprehended as a neighbor. After, contemporary orientation of an individual on happiness is consid- ered as well as the moral qualities necessary for human interactions. The contemporary direction of an individual on happiness is assigned by a hedonistic lifestyle and factor of luck with the emphasizing of contingency of the “hit of jackpot” and the directive on success with brightly expressed elements in the use of chance. Also, transformations of the quality of interactions in the process of concretization of abstract others as neighbors and distants are examined. In liquid modernity others, neighbors and distants, are defined not spatially, but axiologically. At the interpersonal level, where neighbors act, the Other manifests oneself through humanity and activates the virtue of responsibility. At the social level, others are distant people and their interaction is correlated with activation of the virtue of trust. The logic in this research derives the analysis of value grounds of interactions of distant people. Then, the general outline is specified in the defining of moral interactions of distant people in global information networks as a symbol of liquid modernity. Today, the basic moral virtues are qualities unknown till the mid of the 20th century (responsibility) or latent for spiritual space of the Western individual till the end of the previous century (trust). These qualities are necessary for interactions of neighbors and distants in the conditions of liquid modernity alongside the virtues of active life, sacrifice, mercy in interpersonal interactions beyond the daily bustle as well as honesty, trustworthy are actual for social interactions.